Harvesting and conservation: are both possible for the palm, Iriartea deltoidea? - Anderson, P.J.; Putz, F.E. (2002)
This paper considers the mechanism of certification to encourage sustainable harvesting and best management practices of Iriartea deltoidea Ruiz and Pavon, in the context of current land use and agricultural management in Amazonian Ecuador. To understand the demographic variables that are critical for population stability, data from five plots in each of three different types (mature, secondary, and disserted) were collected. Matric models were used to develop harvesting simulations through which biological constraints on sustainable harvesting were explored. Results showed that harvesting Iriartea could fit within current land use. Some forest colonists clear pastures to graze cattle, while others devote land to agriculture, including polycultures of annuals and perennials. In either case, palms can be left standing when forests are cleared. Swidden agriculture depends on fallow period during which secondary forest may begin to generate. These secondary forests are ideal locations for extraction of forest products that fit within the cycle of fallow regeneration in areas near human settlements. Sparing Iriartea individuals 5-15 m tall could benefit agriculture, encourage the sustainability of future harvests, and help ensure the future of this palm as a part of the Amazonian landscape. Interview with staff of governmental and non-governmental conservation organizations investigated the policy context for certification as a mechanism for conservation. Establishing guidelines for harvesting requires input from all stakeholders in the decision, not simply an ecological analysis.